Intermediate-term mortality and cardiac transplantation in infants with single-ventricle lesions: Risk factors and their interaction with shunt type - Tweddell, James S.; Sleeper, Lynn A.; Ohye, Richard G.; Williams, Ismee A.; Mahony, Lynn; Pizarro, Christian; Pemberton, Victoria L.; Frommelt, Peter C.; Bradley, Scott M.; Cnota, James F.; Hirsch, Jennifer; Kirshbom, Paul M.; et al. (The Journal of thoracic and cardiovascular surgery, 2012)
The study objective was to identify factors associated with death and cardiac transplantation in infants undergoing the Norwood procedure and to determine differences in associations that might favor the modified Blalock–Taussig shunt or a right ventricle-to-pulmonary artery shunt. We used competing risks methodology to analyze death without transplantation, cardiac transplantation, and survival without transplantation. Parametric time-to-event modeling and bootstrapping were used to identify independent predictors. Data from 549 subjects (follow-up, 2.7 ± 0.9 years) were analyzed. Mortality risk was characterized by early and constant phases; transplant was characterized by only a constant phase. Early phase factors associated with death included lower socioeconomic status (P = .01), obstructed pulmonary venous return (P < .001), smaller ascending aorta (P = .02), and anatomic subtype. Constant phase factors associated with death included genetic syndrome (P < .001) and lower gestational age (P < .001). The right ventricle-to-pulmonary artery shunt demonstrated better survival in the 51% of subjects who were full term with aortic atresia (P < .001). The modified Blalock–Taussig shunt was better among the 4% of subjects who were preterm with a patent aortic valve (P = .003). Lower pre-Norwood right ventricular fractional area change, pre-Norwood surgery, and anatomy other than hypoplastic left heart syndrome were independently associated with transplantation (all P < .03), but shunt type was not (P = .43). Independent risk factors for intermediate-term mortality include lower socioeconomic status, anatomy, genetic syndrome, and lower gestational age. Term infants with aortic atresia benefited from a right ventricle-to-pulmonary artery shunt, and preterm infants with a patent aortic valve benefited from a modified Blalock–Taussig shunt. Right ventricular function and anatomy, but not shunt type, were associated with transplantation.